TRADITIONAL PRACTICES OF ETHNIC PEDAGOGIZATION OF ENVIRONMENTAL EDUCATION IN SCHOOLS OF THE REPUBLIC DAGESTAN - Bika Sh. Alieva; Zaira Kh. Omaraskhabova; Indira O. Bagamaeva (Юг России: экология, развитие)
Abstract. Aim. The article suggests some solutions to the problems of ecological education by means of the popular pedagogy, the basis of which is the new paradigm of the transition of the ethno-cultural environment. Discussion. The research view to the problem of using the educational resource of nature is aimed at seeking for ethical and ecological guidance for the upbringing of the younger generation. The course taken by the society on the upbringing of an individual of a high ecological culture should be based on the educational potential of the popular pedagogy which assumes a reasonable attitude towards the nature. The authors substantiate the need for an integrated approach to environmental education in interrelation with morality and, especially patriotism. The paper reveals some pedagogical conditions for teaching ethno-ecological traditions, the use of which promotes the formation of a value perception and attitude to the nature. Conclusion. The use of the spiritual and moral potential of ethno-ecological traditions in the teaching and upbringing process of the youth will contribute to the ethno-pedagogization of the educational institutions as well as the formation of a high ecological culture of the youth. Ethno-pedagogization of the educational process is seen as a driving force that helps create conditions for the realization of the regional component of the content of education.